Diet quality and nutrient density in subjects with metabolic syndrome: Influence of socioeconomic status and lifestyle factors. A cross-sectional assessment in the PREDIMED-Plus study. Issue 4 (April 2020) - Cano-Ibáñez, Naomi; Gea, Alfredo; Ruiz-Canela, Miguel; Corella, Dolores; Salas-Salvadó, Jordi; Schröder, Helmut; Navarrete-Muñoz, Eva M .; Romaguera, Dora; Martínez, J. Alfredo; Barón-López, F. Javier; López-Miranda, José; Estruch, Ramón; et al.
Summary: Background: Socioeconomic disparities and lifestyle factors are likely to determine the overall quality of the diet. In addition, overeating is compatible with inadequate micronutrient intake and it can lead to adverse health outcomes. Objective: To assess adequacy of dietary nutrient intake and to investigate the influence of socioeconomic and lifestyle factors on nutrient density in a large primary cardiovascular prevention trial conducted in healthy participants with metabolic syndrome (MetS) to assess the cardiovascular effects of an energy-restricted Mediterranean diet (PREDIMED-Plus). Methods: Baseline cross-sectional analysis of the PREDIMED-Plus trial with 6646 Spanish participants (aged 55–75 years in men and 60–75 years in women) with overweight/obesity and MetS. Energy and nutrient intake (for 10 nutrients) were calculated using a validated 143-item Food Frequency Questionnaire (FFQ) and nutrient density was estimated dividing the absolute nutrient intake by total energy intake. The prevalence of inadequate intake was estimated according to dietary reference intakes. Multivariable linear regression models were fitted to examine associations between socioeconomic status or lifestyle factors and nutrient density. Results: A considerable proportion of the screened participants showed a deficient intake of vitamins A, D, E, B9, calcium, magnesium and dietary fibre. Inadequate intake of four or more of the ten nutrients considered was present in 17% of participants. A higher nutrient density was directly and significantly associated with female sex, higher educational level and a better adherence to the Mediterranean diet. Lifestyle factors such as non-smoking and avoidance of sedentary lifestyles were also independently associated with better nutrient density. Conclusions: Patients with MetS, despite being overweight, exhibited suboptimal nutrient intake, especially among men. Low nutrient density diet can be largely explained by differences in socioeconomic and lifestyle factors. These results highlight the importance of focussing on nutritional education in vulnerable populations, taking into account nutrient requirements.